Characterization of cis-4-hydroxy-D-proline dehydrogenase from Sinorhizobium meliloti. Issue 1 (2nd January 2018) - Watanabe, Seiya; Morimoto, Daichi; Fukumori, Fumiyasu; Watanabe, Yasuo
Abstract: The hypO gene from Sinorhizobium meliloti, located within the trans -4-hydroxy-L-proline metabolic gene cluster, was first successfully expressed in the host Pseudomonas putida . Purified HypO protein functioned as a FAD-containing cis -4-hydroxy-D-proline dehydrogenase with a homomeric structure. In contrast to other known enzymes, significant activity for D-proline was found, confirming a previously proposed potential involvement in D-proline metabolism.